(Ir)racionalidade tributária brasileira no esforço pela performance: no liame entre a agressividade fiscal e o seu custo transacional - Lima, Lauro Vinício de Almeida (2020)
The research aimed to analyze in Brazilian publicly traded companies the reflex of the level of fiscal aggressiveness related to the taxes on profit in the financial and economic performance. The proposed thesis was that the limited rationality inherent in the decision-making process for implementing fiscal aggressiveness does not allow decision makers to fully glimpse the transaction costs involved and, therefore, adopt levels of fiscal aggressiveness in which the benefits obtained do not offset the costs incurred. As a result, the level of fiscal aggressiveness practiced in publicly traded Brazilian companies, related to taxes on profits, has a negative impact on economic and financial performance. Thus, based on the theories of limited rationality and transaction costs, the research analyzed 219 non-financial companies listed in Brazil Bolsa Balcão (B3), through an unbalanced panel, in the period from 2010 to 2019. Contemplating the market Brazilian, the study identified a proxy for measuring the level of aggressiveness in Brazilian companies and through the Generalized Method of Moments System (GMM-SYS), in a dynamic panel, the study verified the effect of the difference between the effective tax rate of the previous year and the sector average on the level of fiscal aggressiveness (bias of aversion to taxes), examined the effect of the level of aggressiveness on the transaction costs of companies and, finally, analyzed the reflection of the level of fiscal aggressiveness practiced by Brazilian companies in their economic and financial performance. As contributions, for academia and society, this work discussed the transaction costs involved in the practical adoption of fiscal aggressiveness, which may not be properly measured in course of the process decision for implementing fiscal aggressiveness, thus bringing new perspectives to the theme. As performance measures, the study used ROA, ROE and EBIT; as a proxy for tax aversion, the difference between the company's effective rate and the sector's average effective rate; and, for measuring the transaction cost, the difference between net current revenues and EBIT. The results obtained in this research validated the proposed thesis. Evidence was found that aversion to income taxes, based on past negative experiences, raised the level of fiscal aggressiveness in publicly traded Brazilian companies. Also, evidence was found that the level of fiscal aggressiveness increased the transaction costs of companies. And, finally, I find evidence that the level of fiscal aggressiveness practiced has a negative influence on economic and financial performance. The findings increase the discussion on the topic, by clarifying that the limited rationality inherent in the decision process to adopt fiscal aggressiveness, concealed the transaction costs involved, overshadowing the cost and opportunity analysis of fiscal aggressiveness in the Brazilian corporate environment. Understanding this reality is important because analysis of the implementation of fiscal aggressiveness should consider, as a priority, its cost-benefit.